Design and Construction of Gas Leakage and Detection System in Homes/ Industries. - Waiswa, Hashimu (Kabale University, 2023)
Liquefied Petroleum Gas (LPG) leakage poses great danger in this em where its use has become an important source of energy for industries. homes :incl vehicles alike. A means or avoiding dangers associated with LPG leakage is to install LPG leakage detectors at susceptible areas. The objective of this project therefore is to design a microcontroller bas@@ LPG leakage detection and response system. The system detects LP(; lc,1k,1ge using MQ-(1 gas sensor and alerts the user of the leakage through GSM-based on c,111 and SMS with buzzer. Most importantly, the system helps to respond lo prcwnt accidents. This was achieved using clatasheets in selecting suitable components for the circuit design and using Proteus in simulating the proposed design in order to validate the fec1sibility of the design. When LPG concentration in the air exceeds the set threshold, the system irninedic1kly <1ler1s the user by cc1lling and sending SMS to a specified mobile number stored on the microcontroller and activates the alarm buzzer simultaneously. displaying the information on an LCD. This design provides adequate safety ancl prevents gas wastage and ilcciclents associated with LPG leakage by providing notification of gas leakage and responding quickly. The design is highly recommended to LPC dealers :ind users ;1/ikc.